In Vitro Analysis of Tandem Peptides from Human CD5 and CD6 Scavenger Receptors as Potential Anti-Cryptococcal Agents - Gustavo Mourglia-Ettlin; María Clara González-Porcile; Violeta Planells-Romeo; Antonella Long-Albín; Laura Carrillo-Serradell; Sebastián Miles; Francisco Lozano; María Velasco-de-Andrés (Journal of Fungi, 2024)
Cryptococcus neoformans is included in the World Health Organization fungal priority pathogen list, complied to expedite improved research and public-health interventions. The limited number of available antifungal drugs, their associated toxicity, and the emergence of drug-resistant strains make the development of new therapeutic strategies mandatory. Pattern-recognition receptors (PRRs) from the host’s innate immune system constitute a potential source of new antimicrobial agents. CD5 and CD6 are lymphoid members of the ancient scavenger receptor cysteine-rich superfamily (SRCR-SF) which bind pathogen-associated molecular patterns (PAMPs) of fungal and bacterial origin. Evidence supports the concept that such binding maps to 11-mer sequences present in each of their three SRCR extracellular domains. Herein, we have designed synthetic peptides containing tandems of such 11-mer sequences (namely CD5-T and CD6-T) and analyzed their C. neoformans-binding properties in vitro. Our results show both inhibitory effects on fungal growth and an ability to impact capsule formation and titanization, two critical virulence factors of C. neoformans involved in immune evasion. These effects hold promise for CD5-T and CD6-T peptides as single or adjuvant therapeutic agents against cryptococcosis.